Analysis of Motivation and Public Perception in UNNES Sunday Aerobics Program - Nadyatus Subhey; Anggit Wicaksono (Universitas Negeri Semarang, 2026)
This study aims to comprehensively and systematically analyze the motivational factors and public perceptions in participating in the Sunday Morning Activity (SMA) program organized by the UNNES Gymnastics Student Activity Unit. This study uses a descriptive quantitative approach with convenience sampling techniques involving 50 respondents. The research instrument is in the form of a Likert scale questionnaire designed to measure participants' motivation and perception. The results showed that the motivation level of participants was very high, with intrinsic factors such as happiness being the dominant factor, accompanied by extrinsic factors such as health benefits and social interaction. In addition, participants' perception of the quality of the program was also very positive, which reflected satisfaction with the instructors, facilities, and the overall atmosphere of the activity. These findings show that campus-based community gymnastics programs are able to create a fun experience while encouraging sustainable participation. Therefore, this program has great potential as an effective and sustainable model in the development of people's physical activities.